DINAMIKA HUKUM PEMERINTAHAN DESA - hasjimzoem, yusnani (FIAT JUSTISIA, 2014)
The existence of the village government in Indonesia has been experiencing the dynamics depend on the legal politics of government prevailing at that time. The village as a unit of community has a characteristic that has always been a discussion in every era of reign by the various policies that have been issued. Hence this research only focused on the dynamics of changes in the law on the village and and the things that affect these changes are the implications of the policy change.Â Keywords: Village Government, Changes in the Law on The Village